Flow Assisted Erosion-Corrosion of High Speed Steel (HSS) in Nanofluid Coolant - Asmara, Y. P.; Yap, Chun Wei; Mohd Fazli, Ismail; Khairi, Yusuf (2014)
The use of nano-coolant is suspected to have effects on erosion-corrosion of piping systems in heat exchanger. This study was carried out to determine the erosion corrosion of AISI 316 stainless steel in solutions containing nano particles. The experiments used rotating cylinder electrode (RCE) at rotational speed of 0 -1800 rpm under varying temperature of 30oC-70oC. Corrosion rate was measured using linear polarization resistance (LPR) method and erosion was indicated by measuring average depth of surface of the samples (surface roughness). The results showed that both corrosion rate and surface roughness of samples have increased when temperature and rotation speed increased. The erosion-corrosion effects of nano-coolant were lower in stagnant condition. Comparing with conventional coolant, the nano-fluid showed significant differences. In flow conditions, the effects were remarkable. It was also found that maximum synergism erosion and corrosion were occurred at higher temperature and high rotation speed for both of types solutions.